Dynamic Viscoelastic Properties of Kenaf Fiber as Reinforced Shape Memory Polymer Composites - Khiyon, Nor Hanim; Arshad, Mohd Fadzil; Kamarudin, Mohd Khairul; Muhammad Fauzi, Nurshamimie (International Journal of Sustainable Construction Engineering and Technology, 2024)
This paper comprehensively investigates the dynamic viscoelastic behavior of shape memory polymer composites (SMPCs) reinforced with different weight percentages of kenaf fiber (KF) ranging from 0%, 5%, 10%, 15%, 20%, 30% and 40%. The dynamic mechanical behavior of these composites was characterized using dynamic mechanical analysis (DMA) over a range of temperatures. The objective was to determine the optimal fiber content of KF as reinforcement in SMPCs, specifically on viscoelastic response, storage modulus, loss modulus, damping and glass transition behaviour. The results revealed a clear correlation between the KF contents and the dynamic mechanical properties of SMPCs. The storage modulus significantly improves at higher KF content, particularly at elevated temperatures. Additionally, a quantitative assessment of coefficient C demonstrates strong interfacial bonding between fibers and the matrix in samples 30KF and 40KF. These samples also exhibit higher loss modulus and lower tan delta values, providing evidence for the efficacy of KF in enhancing composite properties. Moreover, higher KF contents induce a shift in the glass transition temperature, signifying enhanced in fiber-matrix interaction and thermal stability. The Cole-cole further demonstrates that at higher KF content, the sample surpasses Neat SMPU, presenting compelling evidence of improved matrix-fiber bonding. Statistical analysis through one-way analysis of variance (ANOVA) substantiates the statistical significance of the dynamic mechanical properties across the different weight percentages of KF-SMPCs. Based on these findings, 30KF is the optimal fiber content, balancing mechanical enhancement and feasible fabrication. This decision is grounded in challenges encountered at 40KF, where ensuring composite homogeneity becomes complex. This study contributes to the growing body of knowledge on utilization of natural fibers in development of advanced polymer composites while maintaining eco-sustainability.